Between pulpit and pew : the supernatural world in Mormon history and folklore - Reeve, W. Paul; Van Wagenen, Michael (Utah State University Press, 2011)
Mormons gave to supernatural legends and events distinctive meanings related to Mormon theology and culture, but such narratives incorporated motifs found in many cultures. Many such historical legends and beliefs continue to find adherents down to the present. In this collection, historians employ folklore to illuminate the cultural and religious history of the Mormon people.